A MODEL TO ANALYZE WEATHER IMPACT ON APHID POPULATION DYNAMICS: AN APPLICATION ON SWALLOWTAIL CATASTROPHE MODEL - MKDK Piyaratne; Zhao Huiyan; Hu Zuqing; Hu Xiangshun; Wang Yu; Wang Bailing (European Scientific Journal, ESJ, 2014)
Aphids are important pests of most of the crops which are greatly affected by weather parameters such as temperature, relative humidity, rainfall, wind and sunshine hours. When applying eco-friendly control measures such as biological control, a good understanding of their population dynamics which is been impacted by above weather parameters is critically important. A number of experiments have been conducted to develop forecasting models or expert systems based on weather parameters as one of their driving variable for identifying the population dynamics of aphids. Considering more weather variables as a function of change of population is a difficult task and mathematical models have not been developed to overcome this for catastrophe theory applications. This research is aimed to develop a method to analyze the overall effect of more weather variables as a weather factor which could specifically be useful for catastrophe theory applications on population dynamics. In this paper a mathematical model is developed using factor analysis to do this task and implemented as a computer program. The model is applied with a swallowtail catastrophe theory model which has been developed to analyze the aphid population dynamics. The mathematical expressions of development of the model, its implementation and the results of the model verification are presented. Simulated results of the program suggest that some catastrophic movements like sudden jumps happening in growth of wheat aphid populations can clearly be explained by considering overall weather effect as the weather factor for population analysis models.